Similarities and differences in risk factors for retinal artery occlusion and stroke. (14th October 2021) - Oerskov, M; Vorum, H; Larsen, T B; Skjoeth, F
Abstract: Background: Retinal artery occlusion and stroke share several risk factors and have been defined as equivalent diseases by the American Heart Association and American Stroke Association (1, 2). Purpose: The purpose of this study was to compare risk factors between RAO and stroke. Similarities and differences were addressed and the pathophysiology of the two diseases discussed. Methods: This study was conducted as a case-control study, using data from the Danish nationwide registries to identify personal information, diagnoses, and prescriptions. Study subjects were included between 1st of January 2000 and 31st of December 2018, resulting in 5683 RAO cases. The cases were matched on year of birth, sex, and year of diagnosis with 5 random stroke patients. Risk factors from up to 5 years prior to the index date were included and associations were investigated with adjusted conditional logistic regression. Results: The clinical risk factors investigated between RAO and stroke showed both differences and similarities. The effect measures for diabetes, renal disease, IHD, AMI, and HF were close to equivalence and we assessed the association between these risk factors and both RAO and stroke were comparable. Differences in the association of the included risk factors between RAO and stroke were identified. The association between AF and stroke was stronger compared to RAO, whereas a stronger association was found between RAO and cataract, glaucoma, RVO, hypertension, and PAD. The shared risk factors for RAO and stroke support the strong association between the two diseases. The shared risk factors are all associated or diseases of the cardiovascular system, supporting thromboembolism as the pathogenesis of both diseases. The identified differences may indicate variations in the pathophysiology for RAO and stroke, respectively. First, the included eye diseases are associated with changes in the pressure gradients of the eye and indicate that these pressure gradients increase the risk of RAO significantly more compared to stroke (3–5). Second, AF is a major cause of cardiogenic embolization (6–9). The stronger association between AF and stroke may indicate that cardiogenic embolization is more prevalent in stroke patients compared to RAO patients. Finally, hypertension and peripheral artery disease are associated with atherosclerotic embolization and the stronger association between both hypertension and peripheral artery disease and RAO may indicate atherosclerotic embolization is the main pathophysiology of RAO (6, 10–12). Conclusion: This study found similarities and differences between the risk factors for RAO and stroke. The results indicated that RAO may be stronger associated with eye diseases and atherosclerotic embolization, whereas stroke may be stronger associated with cardiogenic embolization. FUNDunding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): The Obel Family Foundation